Does chin-throat length relate to oropharyngeal volume, minimum axial area, and polysomnographic indices? - Tantirittiporn, Wachira; Sonsuwan, Nuntigar; Powcharoen, Warit; Jotikasthira, Dhirawat; Sastraruji, Thanapat; Khongkhunthian, Pathawee; Kuharattanachai, Kachaphol; Tripuwabhrut, Kanich (Biomedical Sciences and Clinical Medicine, 2024)
Objective To evaluate the correlation between chin-throat length and oropharyngeal volume, minimum axial area, and polysomnographic indices in patients undergoing orthodontic treatment. Methods The study enrolled 73 patients (35 men and 38 women) who met the inclusion criteria. The face scanner created a 3D facial simulation, and chin-throat length was subsequently measured. 3D CBCT images were used to simulate 2D lateral cephalometric images. Oropharyngeal volume and minimum axial area were determined using Dolphin imaging software, and airway function was assessed through unattended at-home overnight polysomnography. Pearson correlation coefficients were then used to determine the correlations between chin-throat length and oropharyngeal volume, minimum axial area, and polysomnographic indices. Additional correlations were explored between age, BMI, cephalometric variables, and oropharyngeal volume, and minimum axial area. Finally, multiple regression analysis was used to analyse the factors having an influence on the correlations. Results Chin-throat length was positively correlated with oropharyngeal volume and minimum axial area. SNB, ANB, Co-Gn, and Go-Gn were also observed to be positively correlated with oropharyngeal volume and minimum axial area. Multiple regression analysis demonstrated that the factor influencing the correlation of chin-throat length with oropharyngeal volume and with minimum axial area was mandibular length; however, the correlations were only observed among men. No correlation was evident between chin-throat length and polysomnographic indices. Conclusions Chin-throat length is positively correlated with oropharyngeal volume and minimum axial area but has no association with polysomnographic indices. Mandibular length may influence upper airway dimensions.